Помогите решить: Упростите выражение при a=1, и b=-3

0 голосов
51 просмотров

Помогите решить:
Упростите выражение ( \frac{1}{a-b} - \frac{1}{a+b} ): \frac{b}{a-b} при a=1, и b=-3


Алгебра (83 баллов) | 51 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
( \frac{1}{a-b} - \frac{1}{a+b} ): \frac{b}{a-b} = \frac{(a+b)-(a-b)}{(a+b)(a-b)}* \frac{a-b}{b}= \frac{a+b-a+b}{(a+b)(a-b)}* \frac{a-b}{b}= \\\\ = \frac{2b}{a+b}* \frac{1}{b} = \frac{2}{a+b}

при a=1, и b=-3

\frac{2}{a+b}= \frac{2}{1-3} = \frac{2}{-2}=-1
(138k баллов)